Bioprosthetic Valve Fracturing: In vitro Testing of Edwards PERIMOUNT Model P 2900 - Ruge, Hendrik; Alvarez-Covarrubias, Hector A.; Deutsch, Oliver; Alalawi, Zahra; Vitanova, Keti; Lange, Rüdiger (Frontiers in Cardiovascular Medicine, 2022)
Background Bioprosthetic valve fracturing (BVF) results in low gradients following valve-in-valve transcatheter aortic valve replacement (ViV-TAVR). For the commonly used Edwards PERIMOUNT valve data from bench-testing are lacking to provide technical specifications for successful BVF during ViV-TAVR. Methods Using four Perimount 19- and 21-mm valves, in-vitro high-pressure balloon valvuloplasty with the True Dilatation Balloon Valvuloplasty Catheter and Atlas Gold PTA Dilatation Catheter was performed to analyze balloon-oversizing and pressure-thresholds to successfully achieve BVF. Results High-pressure balloons one millimeter larger than the labeled valve size and pressure rates of 20 atm (for Perimount 19-mm) and > 22 atm (for Perimount 21-mm) were required to achieve BVF. Caliper measurements demonstrated 2.5 mm (Perimount 19-mm) and 1.5 mm (Perimount 21-mm) enlarged inner prosthetic diameters after BVF. The Atlas TM Gold PTA Dilatation Catheter achieved BVF with the Perimount 21-mm, whereas the True TM Dilatation Balloon Valvuloplasty Catheter failed in the Perimount 21-mm either for balloon-rupture or pinhole-defect. Conclusion Both 19-mm and 21-mm Perimount P 2900 are amendable to BVF, thereby increasing the inner prosthetic diameter. High-pressure balloons 1 mm larger than the labeled valves are essential for this purpose, and the Atlas Gold PTA Dilatation Catheter alone should ensure success in the 21-mm prosthetics.